y-9=-13

Simple and best practice solution for y-9=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-9=-13 equation:


Simplifying
y + -9 = -13

Reorder the terms:
-9 + y = -13

Solving
-9 + y = -13

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + y = -13 + 9

Combine like terms: -9 + 9 = 0
0 + y = -13 + 9
y = -13 + 9

Combine like terms: -13 + 9 = -4
y = -4

Simplifying
y = -4

See similar equations:

| -4-7w=-11 | | -7+6t=-43 | | 2-4k=-6 | | 8-4k=-24 | | 6+6m=48 | | 2+7n=-19 | | -5+6k=37 | | 1-7k=1 | | 5d+5=55 | | -10-4a=-18 | | 4b-9=11 | | 8+6b=38 | | 4m-3=-23 | | 4+5n=-46 | | 8+6n=-34 | | -4k-8=-16 | | -10-7d=-17 | | -4w+8=-8 | | 7t+3=45 | | 7w-7=42 | | 2b+10=16 | | -7+2w=-1 | | 2m-8=16 | | -5d+8=-27 | | 1+2t=1 | | 7-6w=13 | | 3d-7=23 | | 7+6a=-53 | | 1+3a=4 | | -9+5m=36 | | 4+3d=28 | | -6+2m=2 |

Equations solver categories